Use of lower gastrointestinal endoscopy and fecal occult blood test in the 2007 Swiss Health Interview Survey respondents aged 50 years and older - Spaeth, A.; Zwahlen, M. (Endoscopy, 2013)
Background and study aims: Colorectal cancer (CRC) incidence ranks third among all cancers in Switzerland. Screening the general population could decrease CRC incidence and mortality. The aim of this study was to analyze the use of the fecal occult blood test (FOBT) and lower gastrointestinal endoscopy in a representative sample of the Swiss population aged ≥ 50 years.Methods: Data were analyzed from the 2007 Swiss Health Interview Survey and the prevalence estimates and 95 % confidence intervals were calculated based on all instances of lower gastrointestinal endoscopy and FOBT use, as well as on their use for CRC screening. Uni- and multivariate logistic regression analyses were performed to describe the association between screening use and sociodemographic characteristics, indicators of healthcare system use, and lifestyle factors. Results: In 2007, approximately 36 % of the surveyed people who were aged ≥ 50 years had previously undergone FOBT and approximately 30 % had previously undergone lower gastrointestinal endoscopy. CRC screening use was 7.7 % for FOBT (within the past year) and 6.4 % for lower gastrointestinal endoscopy (within the past 5 years). CRC screening by either method was 13 %. The major determinants of participation in CRC screening were found to be sex (male), physician visits during the past year (one or more), type of health insurance (private), and previous screening for other cancer types.Conclusions: The results of the 2007 Swiss Health Interview Survey indicate rather low levels of FOBT and lower gastrointestinal endoscopy use. Furthermore, the results suggest disparities in the use of CRC screening.